The Effect of Kahoot-Assisted Games Based Learning Model on Students’ Computational Thinking in Science Learning - Fauzatul Ma’rufah Rohmanurmeta; Ivayuni Listiani; Gupi Rohman Nurmansyah (Paedagoria : Jurnal Kajian, Penelitian dan Pengembangan Kependidikan, 2026)
The low level of students' Computational Thinking often stems from a lack of interest, inadequate conceptual understanding, or ineffective teaching methods. This study aims to examine the effect of the Games Based Learning (GBL) model assisted by Kahoot media on the Computational Thinking of elementary school students. This study uses a quantitative approach with a Pre-Experimental design of the One Group Pretest-Posttest type. The data collection technique used is a written test consisting of 5 essay questions. Data analysis uses descriptive tests, normality tests, and hypothesis tests. The results of the paired t-test data analysis show a significance value (p-value) <0.05 which results in the rejection of the null hypothesis (H0) and the acceptance of the alternative hypothesis (H1) clearly indicating a positive and significant effect of this intervention. The average Post-test score (76.93) increased drastically compared to the Pre-test (52.43) which proves that GBL supported by Kahoot is effective in improving students' Computational Thinking abilities in science learning. Based on the findings of this study, it can be concluded that the implementation of the GBL learning model supported by Kahoot media has a positive and significant influence on improving students' Computational Thinking in science learning. Therefore, this model is recommended as a prospective pedagogical strategy. For further studies, it is recommended to use a more robust experimental design with a control group and consider a longer intervention duration, as well as complement it with qualitative evaluation for a deeper understanding.